2008
DOI: 10.1016/j.jcrs.2007.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and kinetics of biofilm formation of Staphylococcus epidermidis to different types of intraocular lenses under dynamic flow conditions

Abstract: Bacterial adhesion to and biofilm development on the IOL surface depended on the characteristics of the biomaterial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 57 publications
2
25
0
1
Order By: Relevance
“…S. epidermidis adhered to a higher extent to the hydrophobic acrylic polymer than to PMMA or the hydrophilic acrylic biomaterial. These results suggest that hydrophobic IOLs are more permissive to S. epidermidis adhesion and growth than hydrophilic IOLs, which is in accordance with previous published data [10,11,12,15]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…S. epidermidis adhered to a higher extent to the hydrophobic acrylic polymer than to PMMA or the hydrophilic acrylic biomaterial. These results suggest that hydrophobic IOLs are more permissive to S. epidermidis adhesion and growth than hydrophilic IOLs, which is in accordance with previous published data [10,11,12,15]. …”
Section: Discussionsupporting
confidence: 93%
“…To overcome these problems, we have designed an in vitro model that more closely resembled intraocular conditions [14]. This model allowed the study of bacterial biofilm formation (from the primary attachment phase to the biofilm maturation phase) on IOLs [15]. Our first results, using a Staphylococcus epidermidis strain, suggested that hydrophobic IOLs were more permissive to bacterial adhesion and growth than hydrophilic IOLs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the number of organisms present on the ocular surface with the preoperative application of topical povidone iodine in the conjunctival sac and periocular skin is the only measure with proven prophylactic value against endophthalmitis (11,12). Endophthalmitis is a potentially sight-threatening infection (13). Detection of endophthalmitis and identification of the causative agent are therefore essential to ensure that rational treatment is given (14), yet routine microbiologic diagnosis relies on time consuming classical culture techniques that offer low sensitivity; indeed, the positivity rates range from 22% to 30% in the aqueous humor and from 40% to 69% in the vitreous humor (15).…”
mentioning
confidence: 99%
“…In ophthalmology, many authors have observed that IOLs, described as being hydrophobic, were more permissive to bacterial adhesion and growth than IOLs described as being hydrophilic [24,25]. Clear-cut relations between bacterial adhesion and IOL surface hydrophobicity are not obtained through these studies.…”
Section: Discussionmentioning
confidence: 94%